The Impact of Age-Diverse Workforce on Organization Performance: Mediating Role of Job Crafting. (March 2021) - Bashir, Mohsin; Hameed, Ammarah; Bari, Muhammad Waseem; Ullah, Raza
The present study explores the impact of the age-diverse workforce (young and old employees) on organization's performance (financial and non-financial) and how job crafting mediates the relationship between age-diverse workforce and organization's performance. By following the administrative survey approach, a total of 450 questionnaires were distributed to the employees of the Pakistan Post Office; however, 288 properly filled questionnaires (64%) were received back. The partial least squares–structural equation modeling (PLS-SEM) approach was used for data analyses. The outcomes of this study explain that there is a significant relationship between both age groups of employees (young and old) and an organization's financial and non-financial performance. In addition, job craft partially mediates the relationship between young-age employees and organization's financial and non-financial performance. However, job crafting fails to mediate the association between old-age employees and organization's financial and non-financial performance. Implications, limitations, and future direction are discussed in the last sections of this study.